Action in Law's Empire: Judging in the Deliberative Mode. Issue 2 (26th July 2016) - Rodriguez-Blanco, Veronica
Abstract : Dworkin advances the view that judges decide legal cases according to constructive interpretation. The aim of constructive interpretation is to justify the coercion of the State. A trivial implication of this view is that officials and citizens will comply with the law because of the justification that has been advanced by judges in their exercise of constructive interpretation. Consequently, neither officials nor citizens comply with the law because they have been coerced or because they have been simply told to do so. But then, it seems that constructive interpretation cannot really provide any guidance since officials and citizens have been asked to accept the interpretation of the law that has been put forward by the judges since arguably, it is the best possible interpretation of what the law is in this particular case. However, why they ought to do so? I will argue that the mistake of the theory of constructive interpretation lies in a misleading and implausible conception of action that believes that action is raw behavioural data and that therefore we need to 'impose meaning', 'value' or 'purpose' on them. I will defend a more plausible conception of action along the classical tradition that understands practice as originating in agency and deliberation. The outcome is that constructive interpretation and its conception of 'imposing meaning' on practice is a theoretical perspective that neglects and misunderstands action and practical reason.